Adverse health events and recommended health research priorities in agility dogs as reported by dog owners - Sellon, Debra C.; Marcellin-Little, Denis J.; McFarlane, Dianne; McCue, Molly; Pechette Markley, Arielle; Shoben, Abigail (Frontiers in Veterinary Science, 2023)
Objective: To understand relative frequency of adverse health events, defined as injuries or infectious diseases, in dogs participating in agility and to determine health research priorities of agility dog owners. Procedures: An internet-based questionnaire distributed to agility dog owners included items related to experiences with infectious diseases and injuries in agility dogs, reasons for retirement of dogs from competition, and ranking of health research priorities. Frequencies of infectious diseases in US geographic regions were compared with Chi-square tests. Research priority rankings were determined as median and interquartile range (IQR) for each topic. Rank-based tests (Kruskal Wallis and Mann-Whitney) compared rankings between participants in different agility organizations, between veterinarian and non-veterinarian competitors, and between respondents who had competed in national championship events and other respondents. Results: There were 1,322 respondents who had competed in canine agility in the previous 6 months, with those respondents reporting a median time competing in the sport of 13 years (IQR = 8 - 20 years); 50% of respondents had competed in at least one national championship agility event in the preceding 5 years. Overall, 1,015 respondents (77%) indicated that one or more of their dogs had been injured and approximately one-third (n = 477, 36%) indicated that one or more dogs had likely acquired one or more infectious diseases as a result of agility activities. Specific types of infectious diseases acquired varied by geographic region in the US. Research priority rankings were similar regardless of preferred agility organization or respondent experience. The highest-ranking research topics were identification of risk factors for specific types of injuries, improvements in equipment and understanding of safe course design, and physical conditioning programs to prevent injury. Conclusions and Clinical Relevance: Agility competitors prioritize research in areas that advance understanding of injury prevention in their dogs. Research priorities are nearly uniform among competitors regardless of their preferred agility organization or level of experience, providing a strong rationale for agility organizations to collaborate in research initiatives that improve safety and well-being for dogs competing in the sport. There has been little published research focusing on the high-priority research areas identified by competitors.